Institutional factors and the performance of higher education institutions in the accounting sufficiency exam - Aline Cordeiro Santana; Bruno Barbosa de Souza; Marcos Paulo Tavares Bazet (Revista Ambiente Contábil)
Purpose: Identify the association between institutional factors and student performance in the accounting sufficiency exam.